Recent Evidence Regarding the Association Between Migraine and Suicidal Behaviors: A Systematic Review - Karimi, Leila; Hoppe, Dimi; Burdick, Christine; Buultjens, Melissa; Wijeratne, Tissa; Crewther, Sheila G. (Frontiers in Neurology, 2020)
Objective The review presents a systematic analysis of post 2015-Nov 2019 literature investigating the association between migraine and suicidal behaviours. Introduction Migraine is a common neurological disorder. The prevalence of migraine increases with age from adolescence to adulthood in both sexes, and results in a substantial loss of productivity due to missing days of school or work and need for bed rest. Literature prior to 2015 suggests that migraine is a predictor of suicide. Given the worldwide public health interest in suicide prevention, we examined the literature collected from diverse, predominantly non-European, populations post 2015. Methods The databases used in this systematic review included: Medline, PsycINFO, EMBASE (Ovid), Science Direct (Elsevier), Cochrane and PubMed for all available years of publication from January 2015 onwards. The review included participants aged 16 and over who had been diagnosed with migraines with the following outcomes variables: any suicidality, both fatal and non-fatal, suicidal ideation and suicidal behavior. Results The database searches yielded a total of 542 citations. Following title and abstract screening 460 articles were excluded, a total of 21 citation were evaluated. After full text review and excluding a further 11 non eligible studies, a total of 10 studies were eligible for inclusion in the systematic review. Conclusions Current existing research highlights the important association between the increased risk of suicidal behaviours in clinical and general population among chronic migraineurs with/without aura worldwide. Future studies are needed to facilitate the development of clinical guidelines for risk assessment, targeted interventions and evidence-based treatment of migraine and lessening of the risk of suicide among this vulnerable population.